Partial normalization of hippocampal oscillatory activity during sleep in TgF344-AD rats coincides with increased cholinergic synapses at early-plaque stage of Alzheimer’s disease - Monica van den Berg; Loran Heymans; Daniëlle Toen; Mohit A. Adhikari; Johan Van Audekerke; Marlies Verschuuren; Isabel Pintelon; Winnok H. De Vos; Annemie Van der Linden; Marleen Verhoye; Georgios A. Keliris (Acta Neuropathologica Communications)
Abstract Sleep alterations are known to occur in Alzheimer’s disease (AD), before cognitive symptoms become apparent, and are thought to play an important role in the pathophysiology of AD. However, knowledge on the extent of macro- and microstructural changes of sleep during early, presymptomatic stages of AD is limited. We hypothesize that Aβ-induced perturbations of neuronal activity disrupt this oscillatory activity during sleep at pre-plaque stages of AD. In this study, we aimed to assess hippocampal oscillatory activity during sleep at pre- and early-plaque stages of AD, by performing 24-hour hippocampal electrophysiological measurements in TgF344-AD rats and wildtype littermates at pre- and early-plaque stages of AD. To provide a mechanistic understanding, histological analysis was performed to quantify GABA-ergic, glutamatergic and cholinergic synapses. We observed a differential impact of AD on hippocampal activity during rapid eye movement (REM) and non-REM (NREM) sleep, in the absence of robust changes in circadian rhythm. TgF344-AD rats demonstrated increased duration of sharp wave-ripples during NREM sleep, irrespective of age. Interestingly, a significantly decreased theta-gamma coupling was observed in TgF344-AD rats, prior to amyloid plaque deposition, which was partially restored at the early-plaque stage. The partial recovery of hippocampal activity during REM sleep coincided with an increased number of cholinergic synapses in the hippocampus during the early-plaque stage in TgF344-AD rats, suggestive of basal forebrain cholinergic compensation mechanisms. The results from this study reveal early changes in hippocampal activity prior to Aβ plaque deposition in AD. In addition, the current findings imply an important role of the cholinergic system to compensate for AD-related network alterations, thereby partially restoring sleep architecture and hippocampal activity.